Sociology of Music: Its Essence, History, and Challenges in the Contemporary Context - Bagaskara, Akbar; Audhyati, Alfira (Master Program of Sociology, Universitas Malikussaleh,, 2025)
Music sociology is a discipline that studies the relationship between music and the society around it, how music reflects, shapes, and is influenced by social, cultural, and political dynamics. Using a qualitative approach sourced from scientific articles and relevant books, this paper discusses the essence of music sociology as a bridge between artistic expression and social reality, highlighting the role of music as a means of communication, cultural identity, and a medium of social transformation. The history of music sociology is explored, from its roots in modernism to contemporary theoretical developments that integrate interdisciplinary approaches. In the contemporary context, music is not only a part of popular culture, but also a means of understanding global issues, such as gender equality, human rights, and climate change. Music has become a platform for social protest, a symbol of resistance, and also a place for marginalized groups to voice their identity. It also examines the challenges facing music sociology today, including globalization, digitalization, and homogenization, which affect the diversity of local music and the way people interact with music. Through in-depth analysis, the article emphasizes the importance of a critical approach to music in understanding social dynamics. It also emphasizes the relevance of the sociology of music in bridging cultural gaps, strengthening social solidarity, and opening up discussion on broader humanitarian issues. Therefore, this article provides not only theoretical insights but also practical reflections on the position of music in changing or building society.